2020
DOI: 10.1371/journal.pone.0231243
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status among women of reproductive age from underserved communities in the United States and the associations between depression and physical health. A cross-sectional study

Abstract: Background In 2017, 46.6 million U.S. adults aged 18 or older self-reported as having mental illness of which 52.0% or 24.2 million are women age 18-49. Perinatal depression and anxiety are linked to adverse outcomes concerning pregnancy, maternal functioning, and healthy child development. Methods and findings Using the 2014 Health Center Patient Survey (HCPS), the objectives of the cross-sectional study are to assess the prevalence of self-reported mental health conditions among female patients of reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…A recurring finding in cross-sectional studies is that women are most greatly affected physically and psychologically by the COVID-19 pandemic compared with men [ 9 , 10 ]. In addition to having worse mental health [ 11 , 12 ], women across the reproductive age group also face challenges with diet, physical activity [13] , and household food insecurity [14] . Furthermore, changes in behavioral factors during the COVID-19 pandemic and lockdown include increased intake of total food consumption, decreased adherence to a healthy diet, and increased snacking [15] .…”
Section: Introductionmentioning
confidence: 99%
“…A recurring finding in cross-sectional studies is that women are most greatly affected physically and psychologically by the COVID-19 pandemic compared with men [ 9 , 10 ]. In addition to having worse mental health [ 11 , 12 ], women across the reproductive age group also face challenges with diet, physical activity [13] , and household food insecurity [14] . Furthermore, changes in behavioral factors during the COVID-19 pandemic and lockdown include increased intake of total food consumption, decreased adherence to a healthy diet, and increased snacking [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Depressive women in reproductive age had more than three times the odds of reporting smoking, diabetes, obesity, hypertension, and of having fair or poor self-rated health (Lin et al, 2020). It has also been demonstrated that depression has a detrimental effect on objective and subjective oral health outcomes (Cademartori et al 2018;Kisely et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On average as reported during the year 2017, 1 in 5 adults in the U.S. experience at least one mental illness each year. 62 These findings suggest that many with OUD experience mental health problems but remain undiagnosed and therefore untreated. Behavioral health interventions have shown to increase patient engagement in substance use disorder treatment; 63 therefore, assessment for undiagnosed mental illness following an overdose may result in better treatment initiation rates.…”
Section: Discussionmentioning
confidence: 99%
“…On average as reported during the year 2017, 1 in 5 adults in the U.S. experience at least one mental illness each year. 62 These findings suggest that many with OUD experience mental health problems but remain undiagnosed and therefore untreated.…”
Section: Discussionmentioning
confidence: 99%